INTERCONNECT OF GROUP III- V SEMICONDUCTOR DEVICE AND FABRICATION METHOD FOR MAKING THE SAME - Lee, Cheng-Shih; Chang, Edward Yi; Chang, Huang-Choung (My University, 2007)
An interconnect of the group III-V semiconductor device and the fabrication method for making the same are described. The interconnect includes a first adhesion layer, a diffusion barrier layer for preventing the copper from diffusing, a second adhesion layer and a copper wire line. Because a stacked-layer structure of the first adhesion layer/diffusion barrier layer/second adhesion layer is located between the copper wire line and the group III-V semiconductor device, the adhesion between the diffusion barrier layer and other materials is improved. Therefore, the yield of the device is increased.